PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN SUBSEKTOR AUTOMOTIVE AND COMPONENTS - Hendra, Hendra; Adjani, Sukma Alifa (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research aims to determine and test the effect of current ratio, return on asset, debt to equity ratio, earning per share, and price earning ratio on stock return. This research also aims to compare and strengthen the results of previous studies. By using purposive sampling technique, a sample of 10 companies and 70 data in the automotive and components sub-sector were obtained that met the sample criteria. The data used in this research were obtained from the financial statements of companies in the automotive and components sub-sector listed on the Indonesia Stock Exchange for the 2014-2020 periode. The data were analyzed using descriptive statistics and regression panel with CEM model to testing all hypotheses. The results of this research are return on asset and price earning ratio influence towards stock return. This is because ROA and PER is the key factors that investor seek, so it can rise the stock return. Meanwhile current ratio, debt to equity ratio and earning per share has no effect on stock return.